Inovasi Layanan BUMDes untuk Mempercepat Proses Sertifikasi Halal UMKM Desa Taman - Musthafa Syukur; Muhammad Gufran Riyanto; Muhammad Angga Pramoedita (Transformative Service Journal, 2025)
The acceleration of halal certification has become an urgent need for Micro, Small, and Medium Enterprises (MSMEs), especially amid increasing public awareness of the importance of halal assurance in food and beverage products. MSMEs in Taman Village possess strong economic potential but still face various obstacles in the certification process, including limited access to information, inadequate technical assistance, and administrative barriers. This community engagement program aims to optimize the role of the Village-Owned Enterprise (BUMDes) as a facilitator to accelerate the halal certification process for MSMEs. This study employs the Participatory Action Research (PAR) method, which actively involves MSME actors, BUMDes managers, and village authorities throughout the stages of problem identification, action planning, implementation, and reflection. Data were collected through participatory discussions, in-depth interviews, field observations, and document analysis. The findings reveal that BUMDes holds a strategic position in providing information services, technical support, and administrative guidance, thereby reducing both the time and cost required for halal certification. Through PAR, a more effective and sustainable collaboration model was established among BUMDes, local government, and MSMEs. The study concludes that strengthening BUMDes’ institutional capacity and regulatory support is essential for building a participatory halal ecosystem that is responsive to the needs of MSMEs.